Professionals and social responsibility: Some patterns - Vanderburg, Willem H. (Journal of business ethics, 1989)
Modern professionals are engaged in making things “better,” but the specific advances on the micro-level are increasingly undercut by problems on the macro-level. The content of this “better” is typically guided by values such as efficiency, productivity or cost-effectiveness, which are essentially output over input ratios unable to account for how a specific improvement will fit into the broader human, social and ecological contexts. Hence, micro-level advances lead to fragmentation and a loss of harmony, compatibility and conviviality. The situation is further complicated by the fact that, culturally speaking, science and technology have become good in themselves, making reasonable discourse difficult. This paper concludes with an analogy from an earlier epoch suggesting how the situation may be resolved.